The Influence of Temperature Increase on the Toxicity of Mercury Remediated Seawater Using the Nanomaterial Graphene Oxide on the Mussel Mytilus galloprovincialis - Francesca Coppola; Amadeu M. V. M. Soares; Etelvina Figueira; Eduarda Pereira; Paula A. A. P. Marques; Gianluca Polese; Rosa Freitas (Nanomaterials, 2021)
Mercury (Hg) has been increasing in waters, sediments, soils and air, as a result of natural events and anthropogenic activities. In aquatic environments, especially marine systems (estuaries and lagoons), Hg is easily bioavailable and accumulated by aquatic wildlife, namely bivalves, due to their lifestyle characteristics (sedentary and filter-feeding behavior). In recent years, different approaches have been developed with the objective of removing metal(loid)s from the water, including the employment of nanomaterials. However, coastal systems and marine organisms are not exclusively challenged by pollutants but also by climate changes such as progressive temperature increment. Therefore, the present study aimed to (i) evaluate the toxicity of remediated seawater, previously contaminated by Hg (50 mg/L) and decontaminated by the use of graphene-based nanomaterials (graphene oxide (GO) functionalized with polyethyleneimine, 10 mg/L), towards the mussel Mytilus galloprovincialis; (ii) assess the influence of temperature on the toxicity of decontaminated seawater. For this, alterations observed in mussels’ metabolic capacity, oxidative and neurotoxic status, as well as histopathological injuries in gills and digestive tubules were measured. This study demonstrated that mussels exposed to Hg contaminated seawater presented higher impacts than organisms under remediated seawater. When comparing the impacts at 21 °C (present study) and 17 °C (previously published data), organisms exposed to remediated seawater at a higher temperature presented higher injuries than organisms at 17 °C. These results indicate that predicted warming conditions may negatively affect effective remediation processes, with the increasing of temperature being responsible for changes in organisms’ sensitivity to pollutants or increasing pollutants toxicity.